Research progress on exosomes/microRNAs in the treatment of diabetic retinopathy - Niu, Si-ru; Hu, Jian-min; Lin, Shu; Hong, Yu (Frontiers in Endocrinology, 2022)
Diabetic retinopathy (DR) is the leakage and obstruction of retinal microvessels caused by chronic progressive diabetes that leads to a series of fundus lesions. If not treated or controlled, it will affect vision and even cause blindness. DR is caused by a variety of factors, and its pathogenesis is complex. Pericyte-related diseases are considered to be an important factor for DR in many pathogeneses, which can lead to DR development through direct or indirect mechanisms, but the specific mechanism remains unclear. Exosomes are small vesicles of 40–100 nm. Most cells can produce exosomes. They mediate intercellular communication by transporting microRNAs (miRNAs), proteins, mRNAs, DNA, or lipids to target cells. In humans, intermittent hypoxia has been reported to alter circulating excretory carriers, increase endothelial cell permeability, and promote dysfunction in vivo. Therefore, we believe that the changes in circulating exocrine secretion caused by hypoxia in DR may be involved in its progress. This article examines the possible roles of miRNAs, proteins, and DNA in DR occurrence and development and discusses their possible mechanisms and therapy. This may help to provide basic proof for the use of exocrine hormones to cure DR.